Lonely Beetles Lose Weight: Absence of Conspecific Sounds Negatively Impacts Body Mass in Larval and Adult Passalus Beetles - Andrew K. Davis (Stresses)
For animals that typically live in groups or family units, being isolated from their conspecifics can be stressful. Horned passalus beetles (genus Odontotaenius), inhabit decaying logs in forests in the eastern United States. While not a truly social insect, they do coinhabit logs and maintain family units, and they are known to communicate with each other using stridulations that produce varying types of “chirps”. This project investigated if the auditory environment within these logs affects the beetles, specifically by exposing larval or adult beetles in a lab to sounds of (1) other beetles chirping, (2) no sound, or (3) the sounds of crickets, for varying time periods. Beetles were weighed before and after the exposures to determine changes in body mass. Beetle larvae experienced the slowest growth rates when listening to crickets or no sound, and the highest growth rates when hearing adult chirps. Adult beetles experienced mass losses in the treatments without beetle sounds, and this finding was replicated in three different experiments. The mass loss was greatest in the experiment that had the longest duration. The fact that the mass losses were observed in both the silent treatment, plus the treatment of cricket sounds, indicates that the lack of conspecific sounds (of other passalus beetles) was driving the effect. Surprisingly, there was no added effect of nematode parasitism on adult weight loss. Also, there was no evidence that the beetles were foraging less in the treatments without beetle sound, which suggest those beetles were experiencing elevated metabolism. The reduced growth rates and lost mass are signs that the beetles experienced chronic stress when deprived of the sounds of their kin. Combined, these experiments demonstrate how the acoustic environment, and especially the sounds of other beetles, is important to the lives of these insects, perhaps owing to the fact that they live in dark tunnels.